Cross-Cultural Study of Community Engagement in Second-Generation Immigrants. (July 2019) - Li, Manyu; Lin, Hung-Chu; Li, Liman Man Wai; Frieze, Irene Hanson
This research examined the role of cultural similarity in community engagement of second-generation immigrants (SGIs). While previous findings examined the rate of community engagement in SGIs, it is still unclear what may be associated with a higher community engagement in SGIs. Based on previous research on cultural similarities, we proposed that SGIs who are more culturally dissimilar to the host culture would have a higher host orientation and thus have higher community engagement than SGIs who are more culturally similar. Study 1 used data from the World Value Survey (WVS) 2010-2014 (Wave 6) to test whether region (varied in cultural similarity between SGIs' home culture and the host cultures) was related to the pattern of general community engagement. Hong Kong, which received more culturally similar immigrants, was compared with the United States, which received less culturally similar immigrants. A negative binomial regression analysis (bootstrapped r = 2000) showed a significant Region × SGI Status interaction. Specifically, community engagement was found to be higher in SGIs than children of native-born parents (CNBs) in the U.S. sample, but not in the Hong Kong sample, as predicted. Study 2 extended Study 1 to test the relation between perceived cultural similarity and SGIs' community engagement in a U.S. sample. A sample of 300 U.S. SGIs was recruited through Qualtrics Panels. Bootstrapped ( r = 2000) results showed that lower perceived cultural similarity predicted higher community engagement in host-national communities. This relation was mediated by SGIs' acculturation orientations toward the host culture. In addition, SGIs' acculturation orientations toward the home culture predicted higher community engagement in conational communities.